(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The aim of the study was to assess English language learning difficulties of elementary school students of Punjab in relation to intelligence. The sample of the study was 176 7th grade students of Punjab state. An English language learning difficulty screening test developed by researcher herself was used for data collection. Raven’s: Standard Progressive Matrices (SPM) was used to assess intelligence of elementary school students. The low and high groups of intelligence were formed by applying P25 and P75 cut points-44 students in each group. High intelligent students as compared to low intelligent students have never faced difficulty in the following areas of: Learn class material at slow speed; spend more time to study than classmates; To understand written instructions; and poor handwriting as compared to peers. Low intelligent elementary students as compared to high intelligent elementary students have always faced difficulty in the following areas of: Pronunciating unfamiliar words correctly while reading; and to understand written instructions. More number in low intelligent students as compared to lesser number in high intelligent face problems sometimes in the areas of: To read comprehension; in written expression; poor handwriting as compared to peers; in giving pauses; to grasp ornamental words; and to understand the meaning of almost similar words.